THE EFFECT OF CRUDE PLANTAGO MAJOR LEAVESEXTRACT ON CYTOGENETIC OF HUMAN LYMPHOCYTES - Al-shybany, Raghad; Shafiq, Shatha (Iraqi Journal of Science, 2024)
The results revealed the reduction effect of Mitotic Index and Blast Index byhigher concentration after 1 hr. exposure time significantly but all of the lowerconcentration showed none significant changes on them. The same result wasindicated when cells treated with exposure 10μg/ml of extract for 48h; BI wasdecrease. The extract has no toxic effect on lymphocyte at concentration 1 and10μg/ml for 48h of treatment. After 72h of exposure time BI was significantlydecreased while different values in MI were seen when cells treat with 1-100 μg/mlof extract. Moreover mitosis was inhibited at high concentrations of extract